Senyawa Imunomodulator dari Myrmecodia pendens Merr & Perry - TRIANA HERTIANI; MARIA ULFAH; EDIATI SASMITO (Fakultas Farmasi Universitas Pancasila, 2013)
Myrmecodia pendens Merr & Perry (Rubiaceae) is widely used in Papua as traditional medicine against various diseases. Preliminary study revealed that ethyl acetate fraction has potency to increase mice Balb/c lymphocyte proliferation in vitro. This study aimed to investigate the active compound responsible for the activity. Dried powders of plant tubers were macerated in ethanol 95% followed by solvent evaporation. The crude extract was further fractionated by liquid-liquid partition with n-hexane, ethyl acetate and water, successively. The ethyl acetate fraction was subjected to a silica gel column and separated by vacuum. The subfraction yields were tested on mice Balb/c lymphocytes to observe the influence on lymphocyte proliferation by MTT assay. Total phenolic content of subfractions were determined by Folin-Ciocalteau method. Chemical characteristics of active compound was identified by GC-MS, UV-Vis spectroscopy, IR and H-NMR. The result showed that total phenolic content has no significant correlation to the lymphocyte proliferation activity. Subfraction 7 yielded from ethyl acetate-methanol (7:3v/v) contained a major constituent (78% by GCMS, 83.75% by Densitometry). GCMS and UV spectra suggested a phenolic substructure. IR and H-NMR suggested that the phenolic was glycosilated and had aliphatic moiety.